2020
DOI: 10.1523/eneuro.0395-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

ErbB4 Null Mice Display Altered Mesocorticolimbic and Nigrostriatal Dopamine Levels as well as Deficits in Cognitive and Motivational Behaviors

Abstract: Natural genetic variants of Neuregulin1 (NRG1) and its cognate receptor ErbB4 are associated with a risk for schizophrenia. Whereas most studies on NRG1-ErbB4 signaling have focused on GABAergic interneurons, ErbB4 is also expressed by midbrain dopaminergic neurons where it modulates extracellular dopamine (DA) levels. Here, we report that extracellular steady-state levels of DA are reduced in the medial prefrontal cortex (mPFC; À65%), hippocampus (À53%) and nucleus accumbens (NAc; À35%), but are elevated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 108 publications
(169 reference statements)
0
13
0
Order By: Relevance
“…Later in development, NRG/ErbB4 signaling regulates the maturation of glutamatergic synapses onto GABAergic interneurons (Del Pino et al, 2013; Fazzari et al, 2010; Kotzadimitriou et al, 2018; Vullhorst et al, 2015; Woo et al, 2007; Yang et al, 2013; Yang et al, 2018), particularly parvalbumin (PV)‐positive fast‐spiking interneurons, that modulate critical period plasticity (Gu et al, 2016; Sun et al, 2016) and neuronal network activity (Andersson et al, 2012; Fisahn et al, 2009; Nason Jr. et al, 2011). NRG/ErbB4 signaling in midbrain DAergic neurons also regulates DA homeostasis and cognitive function (Kwon et al, 2008; Namba et al, 2016; Skirzewski et al, 2018; Skirzewski et al, 2020; Yan et al, 2018). Interestingly, both NRG2 and ErbB4 KOs, as well as conditional ErbB4 fl/fl mutant mice that lack the receptor in tyrosine hydroxylase (Th)‐expressing neurons (Th‐Cre; ErbB4 fl/fl ), exhibit imbalances of basal extracellular DA levels in distinct projection areas (Kato et al, 2011; Mizuno et al, 2013; Skirzewski et al, 2018; Skirzewski et al, 2020; Yan et al, 2018) that are reminiscent of the imbalances in DA release reported in the dorsal striatum and dorsolateral prefrontal cortex (DLPFC) of Scz patients (Slifstein et al, 2015; Weinstein et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later in development, NRG/ErbB4 signaling regulates the maturation of glutamatergic synapses onto GABAergic interneurons (Del Pino et al, 2013; Fazzari et al, 2010; Kotzadimitriou et al, 2018; Vullhorst et al, 2015; Woo et al, 2007; Yang et al, 2013; Yang et al, 2018), particularly parvalbumin (PV)‐positive fast‐spiking interneurons, that modulate critical period plasticity (Gu et al, 2016; Sun et al, 2016) and neuronal network activity (Andersson et al, 2012; Fisahn et al, 2009; Nason Jr. et al, 2011). NRG/ErbB4 signaling in midbrain DAergic neurons also regulates DA homeostasis and cognitive function (Kwon et al, 2008; Namba et al, 2016; Skirzewski et al, 2018; Skirzewski et al, 2020; Yan et al, 2018). Interestingly, both NRG2 and ErbB4 KOs, as well as conditional ErbB4 fl/fl mutant mice that lack the receptor in tyrosine hydroxylase (Th)‐expressing neurons (Th‐Cre; ErbB4 fl/fl ), exhibit imbalances of basal extracellular DA levels in distinct projection areas (Kato et al, 2011; Mizuno et al, 2013; Skirzewski et al, 2018; Skirzewski et al, 2020; Yan et al, 2018) that are reminiscent of the imbalances in DA release reported in the dorsal striatum and dorsolateral prefrontal cortex (DLPFC) of Scz patients (Slifstein et al, 2015; Weinstein et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…NRG/ErbB4 signaling in midbrain DAergic neurons also regulates DA homeostasis and cognitive function (Kwon et al, 2008; Namba et al, 2016; Skirzewski et al, 2018; Skirzewski et al, 2020; Yan et al, 2018). Interestingly, both NRG2 and ErbB4 KOs, as well as conditional ErbB4 fl/fl mutant mice that lack the receptor in tyrosine hydroxylase (Th)‐expressing neurons (Th‐Cre; ErbB4 fl/fl ), exhibit imbalances of basal extracellular DA levels in distinct projection areas (Kato et al, 2011; Mizuno et al, 2013; Skirzewski et al, 2018; Skirzewski et al, 2020; Yan et al, 2018) that are reminiscent of the imbalances in DA release reported in the dorsal striatum and dorsolateral prefrontal cortex (DLPFC) of Scz patients (Slifstein et al, 2015; Weinstein et al, 2017). Consistent with the association of the NRG/ErbB4 signaling pathway with a risk for Scz, mice with targeted mutations in either nrg1 , nrg2 , nrg3 , or erbb4 manifest many behavioral abnormalities that are associated with traits observed in Scz (Chen et al, 2010; Hayes et al, 2016; Lu et al, 2014; Muller et al, 2018; Shamir et al, 2012; Skirzewski et al, 2018; Tan et al, 2018; Wen et al, 2010; Yan et al, 2018), and in some studies shown to be ameliorated by antipsychotic treatment (Tan et al, 2018; Yan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Caspr3 interaction in trans with NRG3 NRG3 is a ligand that binds to and activates ErbB4; 37 however, ErbB4 activation has been implicated to increase DA transmission. 38 ErbB4 null mutation seemed to have little effect on DA axonal BSN clusters and axon branches in NAcc (Figures S4A-S4D). These observations suggest that NRG3 regulates DA synapses and transmission in an ErbB4-independent mechanism.…”
Section: Resultsmentioning
confidence: 98%
“…On the contrary, NRG1-ErbB4 signaling was shown to increase DA release; DA levels in the PFC and striatum were reduced in ErbB4 null mice. 38,51 These observations suggest that NRG3 regulates DA synapses in a mechanism independent of ErbB4. Non-based screens for NRG3 binding proteins from a library consisting of many transmembrane molecules implicated in synaptogenesis identified Caspr3 and ErbB4.…”
Section: Llmentioning
confidence: 85%
“…Some SNPs among the PCOS-IVs in the present study play roles in neurotransmitter systems. For instance, rs2178575 lies in an intron of the gene encoding Erb-B2 receptor tyrosine kinase 4 (ERBB4), which is expressed in GABAergic interneurons but also in midbrain dopaminergic neurons, where it regulates dopamine levels by binding to neuregulin 1 (NRG1) (Skirzewski et al, 2020 ). Mice lacking ErbB4 show regional imbalances in basal dopamine levels and fail to increase dopamine release in response to local NRG1 infusion in the dorsal hippocampus, medial pre-frontal cortex and dorsal striatum (Skirzewski et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%